2016
DOI: 10.1038/srep31865
|View full text |Cite
|
Sign up to set email alerts
|

FFPred 3: feature-based function prediction for all Gene Ontology domains

Abstract: Predicting protein function has been a major goal of bioinformatics for several decades, and it has gained fresh momentum thanks to recent community-wide blind tests aimed at benchmarking available tools on a genomic scale. Sequence-based predictors, especially those performing homology-based transfers, remain the most popular but increasing understanding of their limitations has stimulated the development of complementary approaches, which mostly exploit machine learning. Here we present FFPred 3, which is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
87
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 35 publications
1
87
0
Order By: Relevance
“…The prediction of gene function generally proceeds by the transfer of function from genes with experimental evidence to unannotated, or less-annotated, genes that are similar by some measure [42]. While several methods use multiple data types to carry out predictions [31,47,11], many solely rely on evolutionary relationships [16,24,6,10] and are the focus of the current study.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction of gene function generally proceeds by the transfer of function from genes with experimental evidence to unannotated, or less-annotated, genes that are similar by some measure [42]. While several methods use multiple data types to carry out predictions [31,47,11], many solely rely on evolutionary relationships [16,24,6,10] and are the focus of the current study.…”
Section: Introductionmentioning
confidence: 99%
“…MouseFunc 25 , have also played a key role in the development of these methods and have shown that integrative machine learning and statistical methods outperform traditional sequence alignmentbased methods (e.g., BLAST) 22 . However, the performance of these methods is typically strongly affected by the quality of manually-engineered features constructed from either sequence or structure (features that rely heavily on heuristics that in turn require domain-expert knowledge, and in some cases unstable assumptions, thresholds and preprocessing pipelines) 26 . Here, we focus on methods that can take as inputs sequence and features that are readily derived from sequence (such as predicted structure) and do not focus on, or compare to, the many methods that rely on protein networks like GeneMANIA 27 , Mashup 28 , DeepNF 29 , and other integrative network prediction methods.…”
mentioning
confidence: 99%
“…Here, Table 3. Gene ontology (molecular function) prediction performance evaluated on the DeepGO [Kulmanov et al, 2017] benchmark set in comparison to literature results from DeeProtein [zu Belzen et al, 2019], DeepGO [Kulmanov et al, 2017], FFPred3 [Cozzetto et al, 2016], and GoFDR [Gong et al, 2016]. we focus on the domain of molecular function prediction.…”
Section: Task and Datasetmentioning
confidence: 99%
“…we focus on the domain of molecular function prediction. Similar to enzyme class prediction, the first proposed approaches in this field relied on handcrafted features like functionally discriminating residues (FDR) with PSSM [Gong et al, 2016] and classification models consisting of an array of Support Vector Machines [Cozzetto et al, 2016]. Recently, deep learning approaches have raised the bar by using convolutional neural networks [Kulmanov et al, 2017] and residual neural networks [zu Belzen et al, 2019].…”
Section: Task and Datasetmentioning
confidence: 99%
See 1 more Smart Citation